Thermoelectric properties and figure of merit of perovskite-type Sr1−xLaxSnO3 ceramics. Issue 13 (September 2017) - Yasukawa, Masahiro; Ueda, Kazushige; Fujitsu, Satoru; Hosono, Hideo
Abstract: The thermoelectric properties of perovskite-type Sr1−x Lax SnO3 ceramics with x=0.01–0.05 were evaluated from the Seebeck coefficient S, electrical conductivity σ, and thermal conductivity κ measured at high temperatures. The La-doped ceramics were n -type semiconductors exhibiting thermally activated electrical conduction behaviors in the temperature range of 473–1073 K. Eelectron carriers were introduced into the conduction band from doped La atoms up to x=0.03, which was the solubility limit of La at Sr site. The temperature dependence of the κ values for the ceramics was unaffected by both the La content and the microstructures. Estimations of the electronic thermal conductivities by the Wiedemann-Franz law revealed that the phonon thermal conductivities were dominant for all ceramics. The dimensionless figure of merit ZT increased with increasing temperature for all ceramics and reached 0.02–0.05 at 1073 K. In contrast to cubic Ba1−x Lax SnO3 ceramics, bending of the Sn–O–Sn bonds due to octahedral tilting distortion in Sr1−x Lax SnO3 lowered the electron mobility, decreasing the power factor S 2 σ and ZT values, although it effectively reduced the phonon mean free path, decreasing the κ values.